Identifying binge drinkers based on parenting dimensions and alcohol-specific parenting practices: building classifiers on adolescent-parent paired data - Crutzen, Rik (BMC Public Health, 2015)
BACKGROUND: Most Dutch adolescents aged 16 to 18 engage in binge drinking. Previous studies have investigated how parenting dimensions and alcohol-specific parenting practices are related to adolescent alcohol consumption. Mixed results have been obtained on both dimensions and practices, highlighting the complexity of untangling alcohol-related factors. The aim of this study was to investigate (1) whether parents’ reports of parenting dimensions and alcohol-specific parenting practices, adolescents’ perceptions of these dimensions and practices, or a combination are most informative to identify binge drinkers, and (2) which of these parenting dimensions and alcohol-specific parenting practices are most informative to identify binge drinkers. METHODS: Survey data of 499 adolescent-parent dyads were collected. The computational technique of data mining was used to allow for a data driven exploration of nonlinear relationships. Specifically, a binary classification task, using an alternating decision tree, was conducted and measures regarding the performance of the classifiers are reported after a 10-fold cross-validation. RESULTS: Depending on the parenting dimension or practice, parents’ reports correctly identified the drinking behaviour of 55.8 % (using psychological control) up to 70.2 % (using rules) of adolescents. Adolescents’ perceptions were best at identifying binge drinkers whereas parents’ perceptions were best at identifying non-binge drinkers. CONCLUSIONS: Of the parenting dimensions and practices, rules are particularly informative in understanding drinking behaviour. Adolescents’ perceptions and parents’ reports are complementary as they can help identifying binge drinkers and non-binge drinkers respectively, indicating that surveying specific aspects of adolescent-parent dynamics can improve our understanding of complex addictive behaviours.